Help . . . for the technologically impaired. - Roy, Tom (Corrections Today, 1998)
Part of a special section on security and technology. The writer discusses the value and the necessity of learning to use technology because of the benefits that it offers for communication and security. He advises that it is necessary for the individual to initially identify whether they are “technologically impaired” and then to cross the technological bridge. He discusses training as an investment and the utilization of technology.